Measuring inflation expectations: how the response scale shapes density forecasts - Becker, Christoph; Dürsch, Peter; Eife, Thomas A. (AWI discussion paper series, 2023)
In density forecasts, respondents are asked to assign probabilities to a response scale with pre-specified ranges of inflation. In two large-scale experiments, one conducted in the US and one in Germany, we show how the specifics of the response scale determine the responses: Shifting, compressing, or expanding the scale leads to shifted, compressed, and expanded forecasts. Mean forecast, uncertainty, and disagreement vary by several percentage points. The findings have implications for survey design and for central banks' optimal adjustment of the response scales during times of high inflation.
Keywords: Graue Literatur